Result of Internal Fixation of Femoral Shaft Nonunion with Implant Failure by SIGN Interlocking Nail at Rajshahi Medical College Hospital - Hossain, Mohd Alamgir; Shamima, Mosammat Nargis; Iqbal, Ahmed Asif; Haque, Md Enamul; Parvez, Md Qumruzzaman; Ahsanuzzaman, Md (TAJ: Journal of Teachers Association, 2018)
This prospective study on result of internal fixation of femoral shaft nonunion with implant failure by SIGN interlocking nail was carried out during the period of January 2009 to December 2016at Rajshahi Medical College Hospital, Bangladesh. Mean age of the patient was 34 years (11-70 years), majority of the patients were male (76%), injury was due to high energy trauma (88%), right side involvement was more (68%).Closed exchange nailing was done in 28 cases (56%) and open nailing was done in 22 cases (44%). In the open cases previous implants were removed, refreshening of the fracture ends was done. Antegrade or retrograde SIGN interlocking nailing depend on the site involvement. Reaming materials were used as internal bone graft in all the cases. Autogenouscancellous bone graft was given in 5 cases due to comminution at fracture site (2 cases) and severe osteoporosis (3 cases). The final outcome satisfactory result was found in 44 (88%) cases and unsatisfactory result in 6 (12%) cases. TAJ 2017; 30(1): 11-16